Adverse immunological responses against non-viral nanoparticle (NP) delivery systems in the lung. Issue 1 (1st January 2021) - de Braganca, Leonor; Ferguson, G. John; Luis Santos, Jose; Derrick, Jeremy P.
Abstract: There is a large, unmet medical need to treat chronic obstructive pulmonary disease, asthma, idiopathic pulmonary fibrosis and other respiratory diseases. New modalities are being developed, including gene therapy which treats the disease at the DNA/RNA level. Despite recent innovations in non-viral gene therapy delivery for chronic respiratory diseases, unwanted or adverse interactions with immune cells, particularly macrophages, can limit drug efficacy. This review will examine the relationship between the design and fabrication of non-viral nucleic acid nanoparticle (NP) delivery systems and their ability to trigger unwanted immunogenic responses in lung tissues. NP formulated with peptides, lipids, synthetic and natural polymers provide a robust means of delivering the genetic cargos to the desired cells. However NP, or their components, may trigger local responses such as cell damage, edema, inflammation, and complement activation. These effects may be acute short-term reactions or chronic long-term effects like fibrosis, increased susceptibility to diseases, autoimmune disorders, and even cancer. This review examines the relationship between physicochemical properties, i.e. shape, charge, hydrophobicity, composition and stiffness, and interactions of NP with pulmonary immune cells. Inhalation is the ideal route of administration for direct delivery but inhaled NP encounter innate immune cells, such as alveolar macrophages (AM) and dendritic cells (DC), that perceive them as harmful foreign material, interfere with gene delivery to target cells, and can induce undesirable side effects. Recommendations for fabrication and formulation of gene therapies to avoid adverse immunological responses are given. These include fine tuning physicochemical properties, functionalization of the surface of NP to actively target diseased pulmonary cells and employing biomimetics to increase immunotolerance.